UPAYA DIGITALISASI GUNA PENGOPTIMALAN PENJUALAN PERINTIS KERIPIK PISANG RUMAHAN MELALUI REPACKAGING DAN PENGENALAN MARKET PLACE - Ade Ulul Azmi; Ruli Saefudin; Risna Zulfa Musriroh (Laporan Upaya Nyata Inovasi Ilmu Komputer, 2024)
MSMEs in Lumajang Regency, including banana chip producers, experienced a drastic decline following the COVID-19 pandemic. Bananas are a potential natural resource with superior varieties, namely Agung bananas and Kirana bananas. However, banana chips production has not utilized this potential optimally, causing inequality in the agricultural sector and food security. As a solution, community service has established partnerships with industry players who are able to guarantee the quality of banana chips. Mrs. Sulasmi, a small industry player was chosen to develop "Leunah" banana chips which are free of preservatives and dangerous ingredients. This collaboration aims to improve the local economy and alleviate poverty in accordance with SDG's 1 and SDG's 8. This research uses a descriptive method with a qualitative approach in partnership with "Leunah" Banana Chips in Kunir District, Lumajang Regency. The data used consists of primary data through field observations and secondary data in the form of documents, interviews and observations. Updates to conventional production methods were carried out for efficiency, such as the use of dynamo banana chopping machines and oil draining machines. Digitalization efforts through repackaging and promotions on social media and marketplaces are being carried out so that this small industry can survive and expand the market.